Remembering in blue: Toast to the memory of Ricardo Llopesa - José Siles González (Universidad de Alicante, 2019)
This obituary describes Ricardo Llopesa's career as a writer, poet and literary critic and recalls some of the experiences shared with the author with a Nicaraguan poet.